The Culture of Islamic Education in Dayah: A Holistic-Integrative Perspective - Marzuki Marzuki; Teuku Zulkhairi; Suriana Suriana; Mumtazul Fikri; Hayati Hayati (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Globally, there is a recognized need to develop resilient, culture-based educational models that effectively integrate traditional values with modern challenges. This study aimed to analyze the relationship between cultural elements and the educational system in Acehnese dayah (traditional Islamic boarding schools) by employing a holistic-integrative approach. Data were collected through observation, in-depth interviews, and document analysis at two major dayah in Aceh: Dayah Babussalam Al-Hanafiyyah and Dayah MUDI Mesra Samalanga. Findings reveal that the dayah educational system is intricately linked to seven cultural elements (e.g., knowledge, social organization, religion), forming a unique educational ecosystem. Key mechanisms, including the halaqah method, the use of classical Islamic texts (kitab kuning), and spiritual arts (zikir), facilitate the transmission of religious, social, and spiritual identity. This system both preserves classical Islamic values and demonstrates gradual adaptation to modernity. Islamic education in Acehnese dayah represents a resilient, culture-based learning model that successfully cultivates religious understanding alongside social and spiritual identity. This research offers a robust reference for contextual development of Islamic education, showing how traditional models can be strengthened by integrating local culture while effectively responding to modernization without abandoning their foundational roots.